PENGARUH PEMBERIAN REWARD DAN PUNNISHMENT TERHADAP KINERJA KARYAWAN PROMOTOR REALME SEPULAU SUMBAWA - Irma Suciati; Muhammad Badar; Kartin Aprianti (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2025)
This research aims to determine the influence of giving rewards and punishments on the performance of realme promoter employees on Sumbawa Island, partially and simultaneously. This type of research is associational research with a Likert scale. The type of sample used was saturated sampling with a sample size of 35 respondents, consisting of 14 men and 21 women. Data collection techniques used observation and questionnaires using data analysis techniques using multiple linear regression. The research results show that only giving rewards has a significant effect on the performance of realme promoter employees. However, simultaneously providing rewards and punishments has a significant effect on the performance of realme promoter employees..